Racially equitable diagnosis of cystic fibrosis using next-generation DNA sequencing: a case report - Bennett O. V. Shum; Glenn Bennett; Akash Navilebasappa; R. Kishore Kumar (BMC, 2021)
Abstract Background Cystic Fibrosis (CF) is one of the most prevalent autosomal recessive inherited disease in Caucasians. Rates of CF were thought to be negligible in non-Caucasians but growing epidemiological evidence shows CF is more common in Indian, African, Hispanic, Asian, and other ethnic groups than previously thought. Almost all second-tier molecular diagnostic tools currently used to confirm the diagnosis of CF consist of panels of the most common CF-causing DNA variants in Caucasians. However non-Caucasian individuals with CF often have a different spectrum of pathogenic variants than Caucasians, limiting the clinical utility of existing molecular diagnostic panels in this group. As a consequence of racially inequitable CF testing frameworks, non-Caucasians with CF encounter greater delays in diagnosis and associated harms than Caucasians. An unbiased approach of detecting CF-causing DNA variants using full gene sequencing could potentially address racial inequality in current CF testing. Case presentation We present the case of a female baby from rural India who had a borderline first-tier newborn screening result for CF. Instead of choosing a targeted CF panel for second-tier testing, we used next-generation DNA sequencing to comprehensively analyze the cystic fibrosis transmembrane conductance regulator gene as an unbiased approach for molecular confirmation of CF. Sequencing identified two pathogenic variants that cause CF. One variant (c.1521_1523delCTT) is the most common cause of CF, while the other variant (c.870-1G > C) is absent from all population allele databases and has not been found in the Indian population previously. The rare variant would not have been detected by all currently available targeted CF panels used for second- or third-tier molecular CF testing. Conclusions Our use of full gene sequencing as a second-tier CF test in a non-Caucasian patient avoided the problems of missed diagnosis from using Caucasian-biased targeted CF panels currently recommended for second-tier testing. Full gene sequencing should be considered as the standard methodology of second-tier CF testing to enable equal opportunity for CF diagnosis in non-Caucasians.